Investigating the Caring Behaviors of Undergraduate Nursing Students: A Cross-Sectional Study - Afrooz Bibi, Muhammad Najeeb Khan, Haseena, Nasir Anwar, Amir Sultan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Caring is a state of "feeling and demonstrating concern and empathy for others, showing or having compassion”. Care is practiced by nurses in clinical settings, so clinical education is an essential and integral part of nursing education. Aim: To identify the caring behaviors of undergraduate nursing students of KPK. Methodology: The design was cross-sectional descriptive conducted in the private and public sector nursing institutes of KPK from august 2022 to September 2022. The sample size was 259 using simple random sampling, while the instrument used was a caring behavior inventory (CBI-24) having a Chronbach alpha of 0.96. Mean and standard deviation was calculated for continuous variables while the chi-square test was applied for the association between demographic variables and caring behaviors through SPSS 20. Results: The finding reveal that males were in the majority (86.9%) compared to female students (13.1%). The overall mean score of assurance was higher 39.5±7.6, followed by respecting 22±4.8, while the knowledge and skills mean score was 19.3 ± 4.7, and connectedness 10.8± 3.12. The overall caring behaviors of females were 95±4 higher than male 91.3±1.7. The students of 8th semester caring behaviors were 98.7±1.5 higher than other semesters mean score. Implications: The study will help the nursing institutes and nursing instructor that how nursing students perceived, barriers in caring and how to improve the caring behaviors of undergraduate nursing students in clinical settings. Conclusions: Our study suggests that caring behaviors are perceived by students from the 1st semester of the nursing program. The caring behaviors of the students were significantly associated with gender and semester. Keywords: Care, nursing students, clinical duties, caring skills